Instilling Islamic Values in Realizing Religious Character at SMA Negeri 4 Surakarta - Nursinta, Wulan Tri; Istanto, Istanto (Journal of Educational Sciences, 2025)
This research aims to describe the cultivation of Islamic values in realizing religious character in SMA Negeri 4 Surakarta through the implementation of Islamic activities. Data were collected using qualitative research methods through interviews with Islamic religious teachers and then students, observation and document studies. The results of the study show that the cultivation of Islamic values in Islamic activities at SMA Negeri 4 Surakarta has an impact that leads to the formation of students' religious character. This can be seen from the active participation of students in Islamic activities at school and discipline in worship. The conclusion based on the research is that Islamic activities that are carried out in a structured and sustainable manner are a means for students to be able to grow Islamic values and form a generation that has a religious character. Future prospects schools need to innovate in carrying out Islamic activities so that they attract more Muslim students and improve facilities for the implementation of activities so that they can continue to improve. With this research, it is hoped that it can provide insight into the cultivation of Islamic values in school activities so that it can realize religious character in students.